Verdict Prison For Drug Abuse - Fahmi Reza (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Drug abuse crime is becoming increasingly widespread, especially among the younger generation where the younger generation is the main pillar of a nation that can endanger the survival of the nation in the future. There is a difference of perception between law enforcement regarding the criminalization of the offenses related to drug abuse convictions were deemed less appropriate prison committed against to drugs. Scriptwriting non study was conducted using literature study using laws in Act No. 35 of 2009 challenged the Narcotics and the Supreme Court Circular No. 4 of 2010placement of abuse, abusers and drug addicts into rehabilitation institute of medical and social rehabilitation. The conclusion of this script writing is that the administration of prison sentences against offenders in this respect addicts who are victims of drug abuse should not be done and prioritize rehabilitation verdict.Keywords: Verdict Prison; Drug Abuse; Rehabilitation.